TEORI-TEORI PENDIDIKAN ISLAM IBNU KHALDUN - Khairan M Arif (Akademika : Jurnal Teknologi Pendidikan, 2018)
The purpose of this study was to exploit the contribution and work of a scientific one of Islam that is very well known and credited for modern scholarship in the world, named Ibn Khaldun. Ibn Khaldun has delivered outstanding works in the fields of Education, political Science, sociology and history, so it is important to be known by the Muslims and the people of the world in order to provide benefits to modern civilization. Implementing for concept and prinsip of values them need to be concreted in order the values of then can be measured by educational tecnology approach. Methodology this study using the method of LibraryResearch Historical and descriptive, by studying litaratur the library work of Ibn Khaldun and examined historically and descriptive, so that its results can be scientifically and conclusion the right to a work. The results of this research include; Give original knowledge and information about the work and services of modern scholarship in the IbnKhaldun and the view as well as the theories of IbnKhaldun in Islamic education, like the principles of Education, the purpose of education, Educational Psychology and Islamic Education Curriculum.